THE IMPLEMENTATION OF CHAT BOT AI TO ENHANCE METACOGNITIVE INTERACTION IN INTEGRAL CALCULUS: A CASE STUDY ON THE METHOD OF INTEGRATION - Khoe Yao Tung (Universitas Pelita Harapan, 2025)
This study investigates the integration of Artificial Intelligence (AI) technologies, with a particular emphasis on AI-based chatbots, to enhance metacognitive interactions in the learning of integral calculus, specifically within the domain of integration methods. By cultivating learners’ capacities for planning, monitoring, and evaluating their problem-solving strategies, AI-driven interventions act as catalysts for the development of metacognitive awareness in advanced mathematics instruction. Metacognition, which entails both the awareness and regulation of one’s cognitive processes, constitutes a critical determinant of effective problem-solving proficiency. Employing a case study design, this research explores the utilization of interactive AI chat prompts to deliver real-time guidance, thereby encouraging students to engage in reflective evaluation of their strategies and cognitive approaches. The efficacy of the AI platform is assessed through targeted interventions aimed at fostering metacognitive engagement and enhancing learning outcomes. The findings demonstrate that AI integration significantly supports students in identifying their cognitive strengths and limitations, while promoting the deployment of effective, adaptive problem-solving strategies. By reinforcing metacognitive interaction, this approach equips learners with the cognitive flexibility necessary to navigate complex mathematical tasks, simultaneously contributing to the progression of innovative, technology-enhanced pedagogical practices. Furthermore, the study highlights the role of AI-facilitated personalized learning and adaptive learning environments in supporting differentiated instruction tailored to individual learner profiles.